THE INFLUENCE OF PLAY ON THE FORMATION OF SPIRITUAL CONCEPTS IN PRESCHOOL-AGED CHILDREN - Yunusova Guzal Sultonovna (Bright Mind Publishing, 2025)
Play is not merely a pastime for preschool-aged children but serves as a crucial medium for assimilating moral and ethical values and shaping their worldview. As one of the most effective tools for children to explore the world and develop cognitive frameworks, play holds significant social and educational importance. This article examines the role of play in forming spiritual and moral concepts in preschoolers, analyzing theoretical perspectives from psychology and pedagogy. Key conclusions highlight how play fosters emotional, cognitive, and social development while reinforcing cultural and ethical values.
Keywords: Play, spiritual concepts, preschool age, child personality, national games, moral development.